STRATEGI MARKETING PADA LEMBAGA PENDIDIKAN PROFESI DAN KEWIRAUSAHAAN (LPPK) BHAKTI NUSA SEMARANG - Resti Lusyaningsih; Bagus Kisworo (Jurnal Manajemen Pendidikan, 2026)
This study aims to describe the application of the 7P marketing mix implemented in professional and entrepreneurial education institutions in the hospitality and cruise ship programs in adapting to the digital era, as well as to identify the supporting and inhibiting factors that influence the implementation of marketing strategies. This study uses a descriptive qualitative approach with data collection techniques through interviews, observation, and documentation. The results show that the institution's products, namely hospitality and cruise ship programs based on SKKNI (National Competency Standards), have clear pricing supported by the institution's strategic location, as well as institutional promotion that integrates conventional and digital approaches. Qualified human resources provide responsive services, supported by online service and registration processes and physical evidence in the form of adequate facilities and digital documentation. Digital adaptation accelerates the delivery of information and expands market reach. The high demand for hospitality skills is a supporting factor, while the limitations of digital platform optimization are a hindering factor in the implementation of marketing strategies. These findings provide insights into how institutions in the hospitality sector apply conventional and digital marketing strategies as well as digital transformation in marketing.